Evaluasi Standart Operating Procedure (Sop) Penerimaan Tandan Buah Segar (Tbs) pada PT Fajar Baizuri & Brother di Kabupaten Nagan Raya - Aulia, Fauza; Nugroho, Yoga (Universitas Galuh, 2024)
Standard Operating Procedure (SOP) is a written document that describes the steps to be followed in consistently executing a process. The SOP for handling the reception of Fresh Fruit Bunches (FFB) of Oil Palm at PT Fajar Baizuri & Brothers consists of weighing bridge, grading, and loading map processes. This research aims to evaluate the implementation of SOP in the company. The study employs operations management theory, and data is collected through descriptive analysis and observation. The research findings indicate that during the weighing bridge stage, the personnel do not clean the weighing bridge, and there are adhering impurities. During FFB reception, the personnel do not check the vehicle's position, the vehicle is not properly positioned on the weighing bridge, and they do not use a well-calibrated weighing tool, leading to inaccurate tare weight measurements of the vehicle. In the grading stage, sometimes the personnel fail to clean the working area daily and do not perform grading for the minimum 10% of the core plantation due to variations in the number of trucks carrying FFB. Occasionally, during plasma fruit grading, the leader of the farmer group is absent. After grading, the personnel do not inspect foreign objects that may have been mixed with the FFB. During the loading map stage, the personnel do not fully check the condition of the power pack door, oil level, hose, and cylinder rod before the loading process. After loading, the personnel occasionally fail to properly store the working tools and personal protective equipment according to the SOP.